INTERNATIONAL ETIQUETTE AND DIPLOMATIC PROTOCOL. DIPLOMATIC CONVERSATION AND CORRESPONDENCE - Ahmedov Azimjon; Maxammadolimov Hojiakbar (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: In this article you will learn about International etiquette and diplomatic protocol.